Application of Keyless Security System in Credenza Product Design - Purwanto, Agung Ari; Setiawan, Yogi (JOURNAL OF MECHANICAL ENGINEERING MANUFACTURES MATERIALS AND ENERGY, 2025)
A credenza is a type of furniture commonly utilized as a storage unit for various items, typically equipped with conventional physical locks. These locks, often made from iron, metal, or brass, pose a high risk of theft and require more time to unlock. This study proposes an alternative solution for enhancing storage security systems by incorporating Radio Frequency Identification (RFID) technology. The adoption of a keyless security system based on RFID aims to replace conventional physical locks, offering improved security and efficiency. The primary objective of this research is to evaluate the effectiveness of RFID technology and its practical application in credenza furniture. Experimental results using Medium Density Fibreboard (MDF) as the material indicate that the maximum functional door thickness is 50 mm, with an authentication time of 1.27 seconds. The production process yielded a credenza featuring an RFID Reader Box installed on the inner side of the door, positioned 100 mm from the top edge, and a locking component located on the inner left wall, 115 mm from its edge.